Effect of Public Awareness Campaigns on Calls to Ambulance Across Australia. Issue 5 (May 2015) - Bray, Janet E.; Straney, Lahn; Barger, Bill; Finn, Judith
Abstract : Background and Purpose—: The National Stroke Foundation of Australia has run 12 public awareness campaigns since 2004. Campaign exposure and funding has varied annually and regionally during this time. The aim of this study was to measure the effect of campaigns on calls to ambulance for stroke across Australia in exposed regions (paid or pro bono advertising). Methods—: All ambulance services in Australia provided monthly ambulance dispatch data between January 2003 and June 2014. We performed multivariable regression to measure the effect of campaign exposure on the volume of stroke-related emergency calls, after controlling for confounders. Results—: The final model indicated that 11 of the 12 National Stroke Foundation campaigns were associated with increases in the volume of stroke-related calls (varying between 1% and 9.9%) in regions with exposure to advertising. This increase lasted ≈3 months, with an additional 10.2% relative increase in the volume of the calls in regions with paid advertising. We found no significant additional effect of the campaigns on stroke calls where ambulance services are publicly funded. Conclusions—: The National Stroke Foundation stroke awareness campaigns are associated with increases to calls to ambulance for stroke in regions receiving advertising and promotion. Research is now required to examine whether this increased use in ambulance is for appropriate emergencies. Abstract : Supplemental Digital Content is available in the text.